URGENSI PEMBENTUKAN PERATURAN DAERAH PROVINSI RIAU TENTANG PENCEGAHAN DAN PENANGGULANGAN TINDAK KEKERASAN DI LINGKUNGAN SATUAN PENDIDIKAN - Pratiwi, Hanna; HZ, Evi Deliana; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Schools as an educational environment are mandated as a forum for developingstudents' potential and forming a dignified national character and civilization in order tomake the nation's generatuion more intelligent. However, unfortunately schools to datecannot be considered a completely safe environment for children. Reflecting on RiauProvince itself, recently violence has often occurred in the educational environment itself.However, it turns out that Riau Province does not have regulations governing children'sthat guarantees safety from acts of violence in educational environments. This research isaimed at finding out what is the urgency of forming Riau Province Regional RegulationsConcerning Prevention and Handling of Acts of Violence in Education Unit Environments,then to find out what things need to be regulated in the formation of Riau Province RegionalRegulations Concerning Prevention and Handling of Violence in Education UnitEnvironments.This research uses a sociological approach which will be carried out in RiauProvince, specifically at the Riau Province Education Official, the Women's Empowermentand Child Protection Service, the Riau Province Regional Secretary's Legal Bureau, andthe Riau Community Malay Traditional Institute. This research uses the interview method,then analyzes the data using qualitative analysis which is described into sentences that arearranged systematically. And in making decisions, researchers use deductive thinkingmethods that draw conclusions from a general statement to a specific statement.Based on the research results, there is a lot of urgencies to form a RegionalRegulation for Riau Province Concerning the Prevention and Management of Acts ofViolence in the Educational Unit Environment, namely the number of cases of violence inthe educational environment per year in Riau Province which massively increasing, theminimal contribution of schools in following standards "Child Friendly School" program,lack of school transparency, minimal contribution from the Education Department incarrying out supervision, limited authority of the STIU for the Protection of Women andChildren, child protection regulations in Riau Province which are considered to be laggingbehind, and minimal coordination between institutions responsible for education in RiauProvince.Keywords: Regional Regulation, Acts of Violence in Educational Environtment